Implementation of Criminal Sanctions Policy in Efforts to Prevent and Handle the Crime of Human Trafficking (TPPO) Based on the Theory of Justice - Hasudungan Sinaga (CV. Syntax Corporation Indonesia, 2023)
The crime of trafficking in persons is considered a new crime in the legal system in Indonesia even though the act of trafficking in persons has been occurring in Indonesia for a long time. This research uses empirical juridical legal research methods, namely legal research regarding the enactment or implementation of normative legal provisions in action at each specific legal event that occurs in society. This research aims to determine criminal sanctions to prevent criminal acts of human trafficking (TTPO), current efforts to prevent and handle criminal acts of human trafficking (TTPO) as well as the implementation of criminal sanctions policies in efforts to prevent criminal acts of human trafficking (TTPO). The results of this research state that Law Number 21 of 2007 concerning the Crime of Human Trafficking is the legal umbrella in this case. In this case, it is known that the formulation of the criminal sanction policy for the crime of trafficking in persons which will be included in the National Criminal Code Bill must be much better than the formulation of the crime of trafficking in persons in positive law. The application of criminal sanctions in efforts to prevent criminal acts of human trafficking (TTPO) is based on the theory of justice stated thar justice can change but the essence of justice always exists in human life and social life.